STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN BUDAYA RELIGIUS DI SMP ISLAM MA’ARIF 02 MALANG - Khoisiria Ainulzana; Anwar Sadullah; Ahmad Subekti (VICRATINA, 2019)
This research was conducted at the SMP Islam Ma’arif 02 Malang which began in May 2019. In this atudy we used the method of observation, interviews and documentation. Methods of analyzing  data by reducing data, presenting data and drawing conclusions, implementing strategies for teachers of Islamic education and establishing religious culture in the morning prayers before learning, PHBI (Commemoration of Islamic Holidays), slaughtering qurban animals, huts Ramadhan. The impact of teacher strategy research on the formation of religious culture students have self-awareness in worship, noble character. Keywords: strategy, teacher, religious culture